1970
DOI: 10.1017/s0025315400004902
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of China Clay on the Bottom Fauna of St Austell and Mevagissey Bays

Abstract: This investigation of the bottom fauna of St Austell and Mevagissey Bays was prompted by the feeling among local fishermen that the increasing amount of china-clay waste being deposited in the bays was adversely affecting the local fishery. Physical pollution on a large scale can harm a fishery in a number of ways. The smothering of shellfish grounds is often to be expected, and where the pollutant contains a high proportion of very fine particles there is the danger that unstable clay banks will build up and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

1972
1972
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 8 publications
2
28
0
Order By: Relevance
“…Some of the inferentially more powerful studies come from the demonstration of broad-scale impact on marine benthos of the dumping of fine sediments associated with clay mining (e.g., Howell and Shelton 1970). Some of the inferentially more powerful studies come from the demonstration of broad-scale impact on marine benthos of the dumping of fine sediments associated with clay mining (e.g., Howell and Shelton 1970).…”
Section: Generalizing Experimental Results Using Meta-analysismentioning
confidence: 99%
“…Some of the inferentially more powerful studies come from the demonstration of broad-scale impact on marine benthos of the dumping of fine sediments associated with clay mining (e.g., Howell and Shelton 1970). Some of the inferentially more powerful studies come from the demonstration of broad-scale impact on marine benthos of the dumping of fine sediments associated with clay mining (e.g., Howell and Shelton 1970).…”
Section: Generalizing Experimental Results Using Meta-analysismentioning
confidence: 99%
“…The bivalves Nucula nitidosa and Corbula gibba both declined in abundance relative to the reference area (Maurer et al 1981) and are also sensitive to the high rates of sedimentation (Howell & Shelton 1970) Multivariate analysis of the community data showed that the 2 sites became significantly different after only 5 mo of disturbance, remaining so throughout the experiment. An increase in abundance of opportunistic species was mainly responsible for the differences in the communities.…”
Section: Species Rank Species Rankmentioning
confidence: 94%
“…Discharge of the waste was reduced in 1970 and finally ceased in 1972. Various surveys have been canied out to assess the effects of the wastes on the benthic communities of the bay (Howell and Shelton, 1970;Portrnann, 1970;Probert, 1975Probert, , 1981. In the latter paper, Probert provides time series data on population changes at a station in the Micaceous residue, a sluny of fine-grained inorganic waste from the china clay industry, was for many Fig.…”
Section: Mevagissey Bay Englandmentioning
confidence: 99%